Measurements of cytoplasmic free Ca2+ concentration in human pancreatic islets and insulinoma cells. - Kindmark, H; Köhler, M; Nilsson, T; Arkhammar, P; Wiechel, K; Rorsman, P; Efendić, S; Berggren, P (1991)
In human pancreatic islets an increase in the glucose concentration from 3 to 20 mM raised the free cytoplasmic Ca2+ concentration [( Ca2+]i), an effect being reversible upon withdrawal of the sugar. Depolarization with a high concentration of K+ or the sulphonylurea tolbutamide also raised [Ca2+]i. Addition of extracellular ATP produced a transient rapid rise in [Ca2+]i. Oscillations in [Ca2+]i were observed in the presence of 10 mM glucose. Insulinoma cells responded to glucose and tolbutamide with increases in [Ca2+]i, whereas the sulphonamide diazoxide caused a decrease in [Ca2+]i. These findings confirm previous results obtained in rodent beta-cells.